Development of a Low-cost Arduino-based Patient Monitoring System for Heartrate, Oxygen Saturation and Body Temperature Parameters - Karnadi, Juan; Roihan, Ibnu; Ekadiyanto, Astha; Koestoer, R A (INSTEP Network, 2021)
The implementation of Patient Monitor (PM) in ICU, ICCU, PICU and NICU currently imposes a significantly high cost of investment. According to studies conducted, there are three main parameters required to be measured, which are heartrate (BPM), oxygen saturation (SPO2) and body temperature (T). These are highly needed by the medical personnel to monitor in order to determine patient’s vital state. The low-cost patient monitor prototype (named Patient Monitor 3 Parameters or PM3P) was developed using Arduino platform. In order to measure the parameters, two types of sensor modules were chosen, namely MAX30100 for gathering heartrate and oxygen saturation data and DS18B20 for gathering the body temperature data. The prototyping process also included fixation and finalization of electrical circuit on a printed circuit board (PCB). The PM3P underwent extensive validation process by comparing it to the real industrial PM made by healthcare equipment industry. The comparison was done over data gathered by both system that were conducting the same measurement runs in parallel. Results of validation indicates that the low-cost patient monitor prototype has a slight error of 0,31% for heartrate and 1,59% for oxygen saturation compared to the industrial one. Further improvements for the Arduino based PM3P are also proposed in this paper in order to enhance its reading accuracy, namely calibration.